A MODEL OF FACTORS INFLUENCING ADULTS’ INTENTION TO USE E-WALLET DURING COVID-19 PANDEMIC IN MALAYSIA: A CONCEPTUAL FRAMEWORK - Nurul Labanihuda Abdull Rahman; Sharifah Khairol Musairah Syed Abdul Mutalib; Hasyeilla Abd Mutalib; Sabiroh Md Sabri; Nursyamilah Annuar; Zainatul Shuhaida Abdull Rahman (International Journal of Accounting, Finance and Business, 2022)
Currently, an e-wallet is a revolutionary type of payment system in the development of financial technology (Fintech). Prior e-wallet research has concentrated on factors such as perceived risk and variables from the Technology Acceptance Model (TAM) that influence ewallet usage. During the COVID-19 epidemic, however, the impact of government support and perceived risk on individual behaviour was not well studied yet. Hence, the purpose of this study is to look at the impacts of perceived risk, perceived usefulness, behavioural intention, and government support as potential mediators on the intention to use an e-wallet amongst adults in Malaysia during the COVID-19 epidemic. The participants in this study were individuals aged 25 to 60 years old from Peninsular Malaysia, Sabah, and Sarawak who planned to engage in e-wallet transactions. The partial least square SEM was used to analyse the data (SmartPLS). The study investigates the causes at play as well as a number of difficulties that have arisen as a result of past research findings that have been inconsistent. It also compares the integrated TAM model to other aspects and determines whether TAM is the dominating model in research on adaptation to changing technologies like e-wallets. The outcomes of this study are crucial in establishing which determinants influence e-wallet application in Malaysia during COVID 19. Additionally, e-wallet marketers will learn more about consumer behaviour and the challenges of e-wallet adoption among Malaysian youth. The ministry may indeed help e-wallet companies develop global e-commerce sales.